Varieties of Governance: Rural-Urban Migration and Transformed Governance in Rural China - Lu, Jie (2009)
This dissertation investigates the varied institutional foundations of local governance in rural China with central emphasis on the role of communal structures and rural-urban migration. Instead of treating indigenously developed institutions (IDIs) and externally imposed institutions (EIIs) as competing variables as in most other contemporary research on local governance, this dissertation develops a theoretical framework exploring the interaction between the two types of institutions in sustaining local governance as well as analyzing how community structural features shape this interaction and influence their respective efficacy in sustaining local governance. With the help of a representative national survey in mainland China in 2008 and carefully selected case studies, this dissertation finds that both indigenous institutions and externally imposed institutions can uphold quality governance in local communities, as long as they can efficaciously solve the problems of collective action and accountability. Close-knit communities favor the operation of indigenous institutions; while externally imposed institutions are relatively more competent in half-open communities. However, neither of them can survive and perform effectively in atomized communities due to the lack of a minimal level of coordination among community members. As outward migration challenges rural communities in an uneven way and transforms communal structures to various extents, it is likely to observe a variety of institutional foundations sustaining local governance in Chinese villages. === Dissertation